Anemia in Pregnancy With CKD - Margriet F.C. de Jong; Elizabeta Nemeth; Pien Rawee; Kate Bramham; Michele F. Eisenga (Kidney International Reports)
Chronic kidney disease (CKD), anemia, and iron deficiency are global health issues affecting individuals in both high-income and low-income countries. In pregnancy, both CKD and iron deficiency anemia increase the risk of adverse maternal and neonatal outcomes, including increased maternal morbidity and mortality, stillbirth, perinatal death, preterm birth, and low birthweight. However, it is unknown to which extent iron deficiency anemia contributes to adverse outcomes in CKD pregnancy. Furthermore, little is known regarding the prevalence, pathophysiology, and treatment of iron deficiency and anemia in pregnant women with CKD. Therefore, there are many unanswered questions regarding optimal management with oral or i.v. iron and recombinant human erythropoietin (rhEPO) in these women. In this review, we present a short overview of the (patho)physiology of anemia in healthy pregnancy and in people living with CKD. We present an evaluation of the literature on iron deficiency, anemia, and nutritional deficits in pregnant women with CKD; and we evaluate current knowledge gaps. Finally, we propose research priorities regarding anemia in pregnant women with CKD.